The Analysis of Factors Driving Consumer Engagement and Purchase Intention in E-Commerce Live Streaming - Aulianur, Felicia Fajr; Purwanegara, Mustika Sufiati (Mandalika Journal of Business and Management Studies, 2024)
The rise of e-commerce has enabled consumers to shop anytime and anywhere, access extensive product descriptions, read reviews, compare a wide range of products and prices, and take advantage of offers. Moreover, interactive and personalized shopping experiences have become possible through the latest innovation in e-commerce: live streaming. E-commerce live streaming allows real-time interaction with sellers, combining engagement and convenience, which is highly favored among consumers in Indonesia. One of the main factors influencing the selection of live streaming platforms is the promotional offers provided, as most shopping behaviors are driven by attractive offers. In addition to promotions, the presence of hosts and their interactivity in leading live streaming sessions play a crucial role. Hosts ability to interact with viewers, present informative content, and provide personalized recommendations effectively enhances consumer engagement and purchase intention. However, many local businesses, particularly SMEs, suffer losses due to ineffective host and promotional strategies during live streaming sessions that fail to attract consumers. Therefore, this research aims to provide valuable insights for optimizing live streaming strategies, helping hosts develop more effective approaches and strategies to drive sales in a competitive market. This study focuses on analyzing which host gender, host interactivity, and promotions are more effective strategies in driving higher consumer engagement and purchase intention. The research examines 864 live stream sessions from the three most used and favored e-commerce live streaming platforms in Indonesia: Shopee Live, TikTok Live, and Tokopedia Play. This research applied a descriptive research design with an observational method. The data was analyzed using Descriptive Analysis, Chi-Square Test, Post Hoc Test, and Correlation Analysis through SPSS. The results indicate that host interactivity and promotion are significantly associated with consumer engagement and purchase intention, while host gender does not show a significant association. Moreover, female hosts, responsiveness in interactivity, and flash sales as a promotional strategy appear to be more effective in achieving higher consumer engagement and purchase intention compared to others across all e-commerce live streaming platforms. Shopee Live also emerges as the e-commerce live streaming platform that generates the highest consumer engagement and purchase intention compared to other platforms. The correlation analysis reveals a strong positive relationship between consumer engagement and purchase intention, indicating that higher levels of consumer engagement are associated with higher purchase intentions. These findings highlight the importance of attractive host and promotional strategies in live streaming to maximize consumer engagement and purchase intention in the competitive landscape of e-commerce live streaming.